POLITICAL MESSAGES OF RIA NORSAN AND KRISANTUS IN THE PILKADA KALBAR 2024: A REVIEW FROM THE PERSPECTIVE OF NARRATIVE PERSUASION AND ELM - Sagita, Endy (TOPLAMA, 2025)
Ria Norsan, an ethnic Malay from Mempawah, is the incumbent Deputy Governor of West Kalimantan who has served since 2019. He is running in the contestation of Pilkada Kalbar 2024 as a candidate for Governor alongside with Krisantus Kurniawan, an ethnic Dayak from Sintang, also an incumbent member of the House of Representatives of the Republic of Indonesia (DPR-RI) since 2019 representing the electoral district of West Kalimantan II (Sanggau, Sintang, Melawi, Kapuas Hulu and Melawi Regencies), who is carried as a candidate for Deputy Governor. Now, both are competing in the contestation of the 2024 West Kalimantan Regional Election (Pilkada Kalbar 2024) as a Candidate Pair (paslon) for West Kalimantan Governor Candidate (Cagub) and Deputy Governor Candidate (Cawagub) Number 2. The research method used in this paper is a qualitative approach with content analysis from the perspective of Narrative Persuasion and Elaboration Likelihood Model (ELM). Data were collected through literature studies and media news to identify the political messages of this pair throughout Pilkada Kalbar 2024. The results showed that candidate number 2 conveyed clearly and straightforwardly to be able to create interpersonal relationships with the community through the narratives built. The conclusions of this paper include the need to combine political messages to be balanced between peripheral and central channels in the ELM approach. This combination is expected to gain votes for both and smooth the political path in the Pilkada Kalbar 2024. Suggestions for further research are to analyze political messages using other perspectives to enrich the repertoire of readers and provide valuable input for those who will contest.